2019
DOI: 10.1136/bmjopen-2018-022842
|View full text |Cite
|
Sign up to set email alerts
|

Prostate care and prostate cancer from the perspectives of undiagnosed men: a systematic review of qualitative research

Abstract: ObjectivesTo summarise and evaluate evidence from men who had not been diagnosed with prostate cancer about their perspectives on prostate care and prostate cancer.DesignA systematic review of qualitative research, on the perspectives of non-cancerous men regarding prostate cancer prevention and care.SettingA wide range of settings including primary and secondary care.ParticipantsMen from varied demographic backgrounds ranging between 40 to 80 years of age.Data sourcesThree databases (Ovid MEDLINE, Informit, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Explanations based on allusions to “Australian masculinity”, whether or not they reflected the participants’ own perspectives, are consistent with results of other research that found the masculine stereotype to be one of stoic, silent endurance, in which help-seeking is unmanly [14]. This hegemonic masculinity has a long history and is not confined to Australia [15, 16]; vigilance and action are necessary to counteract its effects.…”
Section: Discussionsupporting
confidence: 76%
“…Explanations based on allusions to “Australian masculinity”, whether or not they reflected the participants’ own perspectives, are consistent with results of other research that found the masculine stereotype to be one of stoic, silent endurance, in which help-seeking is unmanly [14]. This hegemonic masculinity has a long history and is not confined to Australia [15, 16]; vigilance and action are necessary to counteract its effects.…”
Section: Discussionsupporting
confidence: 76%
“…Existential fear could also be perceived as a sign of weakness. Eventually, this construct of masculinity made some men avoid situations that could make them appear weak [ 15 ]. This further emphasizes the importance of an approach that maps individual beliefs and experiences that affects their health behaviors [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst several studies address men’s information needs and emotional challenges after a PCa diagnosis, few studies have focused on these aspects before a PCa diagnosis [ 15 , 16 ]. Little is known regarding men’s perception of the possible emotional strain in the diagnostic phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter study performed in the Netherlands reported that 28% of the patients had elevated anxiety and depressive symptoms before a breast cancer screen, 14 and a cancer diagnosis is known to cause trauma for most patients. 15 While infection or prostate enlargement, as well as PC, can be a cause of elevated PSA levels 16 individuals often feel restless and anxious (PSA anxiety) if they learn that their levels are above normal. 17 PNB is also recommended for some patients with normal PSA levels who had prostate nodules observed by MRI or abnormal DRE results.…”
Section: Introductionmentioning
confidence: 99%